Surface Architecture Design of LiNi0.8Co0.15Al0.05O2 Cathode with Synergistic Organics Encapsulation to Enhance Electrochemical Stability. Issue 21 (17th September 2020) - Hu, Guorong; Fan, Ju; Lu, Yan; Zhang, Yinjia; Du, Ke; Peng, Zhongdong; Li, Luyu; Zhang, Baichao; Shi, You; Cao, Yanbing
Abstract: Ni‐rich LiNi0.8 Co0.15 Al0.05 O2 (NCA) material attracts extensive attention due to its high discharge specific capacity, but its distinct drawbacks of rapid capacity decline and poor cycle performance at elevated temperatures and high voltage during charge/discharge cycling restricts its widespread application. To solve these problems, a multifunctional coating layer composed of a lithium‐ion‐conductive lithium polyacrylate (LiPAA) inner layer and a cross‐linked polymer outer layer from certain organic substances of silane‐coupling agent (KH550) and polyacrylic acid (PAA) is successfully designed on the surface of NCA materials, which is favorable for eliminating residual lithium and improving lithium‐ion conductivity, surface stability, and hydrophobicity of NCA materials. In addition, the amount of the coating material is also investigated. A series of characterization methods such as XRD, FTIR, SEM, TEM, and X‐ray photoelectron spectroscopy are used to analyze the morphologies and structures for materials of pristine and modified NCA. It is revealed that the co‐coating layer plays a vital part in reducing the surface residual alkalis and improving the stability of NCA particles; as a result, the modified NCA exhibits a greatly improved rate capability, cycle performance, and low polarization impedance. Abstract : Inside out : An innovative surface architecture with combination of lithium‐ion conductive inner layer and cross‐linked polymer outer layer via a facile LiNi0.8 Co0.15 Al0.05 O2 (NCA) cathode modification strategy was designed and the effect of the multifunctional coating layer on the electrochemical properties is studied. The formation of co‐encapsulating hybrid layer is favorable for reducing residual lithium impurities, and the continuous coating layer could provide unique surface protection against the organic electrolyte to construct a robust interface.